Quality Provision in Interrelated Markets - Ralf Dewenter (Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2003)
This paper analyses the quality provision of interrelated market firms under different market structures both theoretically and empirically.A theoretical model is built,where a media firm offers newspapers in a primary market and advertising space in the secondary market.Furthermore,the media firm is assumed to choose a continuous quality level for advertisements.To test the hypotheses from the theoretical model empirically,we use data on German regional newspapers.The theoretical outcomes as well as the empirical results support the hypothesis that a monopolist provides a higher quality than a duopolist.
urn:nbn:de:gbv:705-opus-1357
Keywords: L20; L15; L10; 330; Quality Provision; Interrelated Markets; Pricing; Market Structure; Zeitungsverlag; Zeitungswerbung; Medienökonomik; Produktqualität; Lieferanten-Kunden-Beziehung; Monopol; Duopol; Dienstleistungsqualität; Theorie